Tính:\(\text{(10^2+8^2+...+2^2)-(9^2+7^2+...+1^2)}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Lời giải chi tiết
9 + 1 = 10 | 8 + 2 = 10 | 7 + 3 = 10 | 6 + 4 = 10 |
5 + 5 = 10 | 1 + 9 = 10 | 2 + 8 = 10 | 3 + 7 = 10 |
4 + 6 = 10 | 10 – 5 = 5 | 10 – 1 = 9 | 10 – 2 = 8 |
10 – 3 = 7 | 10 – 4 = 6 | 10 – 0 = 10 | 10 – 9 = 1 |
10 – 8 = 2 | 10 – 7 = 3 | 10 – 6 = 4 | 10 – 10 = 0 |
1 + 9 = 10 2 + 8 = 10 3 + 7 = 10 4 + 6 = 10 5 + 5 = 10
10 - 1 = 9 10 - 2 = 8 10 - 3 = 7 10 - 4 = 6 10 - 5 = 5
6 + 4 = 10 7 + 3 = 10 8 + 2 = 10 9 + 1 = 10 10 + 0 = 10
10 - 6 = 4 10 - 7 = 3 10 - 8 = 2 10 - 9 = 1 10 - 0 = 10
ời giải chi tiết:
8 + 2 = 10 | 9 + 1 = 10 | 7 + 3 = 10 | 5 + 5 = 10 |
2 + 8 = 10 | 1 + 9 = 10 | 10 – 3 = 7 | 10 – 5 = 5 |
10 – 8 = 2 | 10 – 9 = 1 | 4 + 6 = 10 | 10 + 0 = 10 |
10 – 2 = 8 | 10 – 1 = 9 | 10 – 6 = 4 | 10 – 0 = 10 |
\(\frac{2}{1.2}+\frac{2}{2.3}+\frac{2}{3.4}+\frac{2}{4.5}+\frac{2}{5.6}+\frac{2}{6.7}+\frac{2}{7.8}+\frac{2}{8.9}+\frac{2}{9.10}\)
\(=2.\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+...+\frac{1}{7}-\frac{1}{8}+\frac{1}{8}-\frac{1}{9}+\frac{1}{9}-\frac{1}{10}\right)\)
\(=2.\left(1-\frac{1}{10}\right)\)
\(=2.\frac{9}{10}=\frac{9}{5}\)
Lời giải chi tiết:
2 = 1 + 1 |
6 = 2 + 4 |
8 = 5 + 3 |
10 = 8 + 2 |
3 = 1 + 2 |
6 = 3 + 3 |
8 = 4 + 4 |
10 = 7 + 3 |
4 = 3 + 1 |
7 = 6 + 1 |
9 = 8 + 1 |
10 = 6 + 4 |
4 = 2 + 2 |
7 = 5 + 2 |
9 = 7 + 2 |
10 = 5 + 5 |
5 = 4 + 1 |
7 = 4 + 3 |
9 = 6 + 3 |
10 = 10 + 0 |
5 = 3 + 2 |
8 = 7 + 1 |
9 = 5+ 4 |
10 = 0 + 10 |
6 = 5 + 1 |
8 = 6 + 2 |
10 = 9 + 1 |
1 = 0 + 1 |
2=1+1 6=2+4 8=5+3 10=8+2
3=1+2 6=3+3 8=4+4 10=7+3
4=3+1 7=6+1 9=8+1 10=6+4
4=2+2 7=5+2 9=7=2 10=5+5
5=4+1 7=4+3 9=6+3 10=10+0
5=3+2 8=7+1 9=5=4 10=0+10
6=5+1 8=6=2 10=9+1 1=0+1
Bài 2:
a: 2/6x5/3=10/18=5/9
b: 11/9x5/10=55/90=11/18
c: 3/9x6/8=1/3x3/4=1/4
d: 4/9x12/16=48/144=1/3
e: 25/15x6/7=5/3x6/7=30/21=10/7
f: 6/10x15/20=90/200=9/20
Bài 1
4/5 x 6/7= 24/35
2/9 x 1/2= 2/18= 1/9
1/2 x 8/3= 8/6= 4/3
7/9 x 6/5= 42/45= 14/15
8/7 x 5/9= 40/63
10/11 x 22/15= 220/165= 4/3
Bài 2
2/6 x 5/3= 1/3 x 5/3=5/9
11/9 x 5/10= 11/9 x 1/2= 11/18
3/9 x 6/8= 1/3 x 3/4 =3/12= 1/4
4/9 x 12/16= 4/9 x 3/4= 12/36= 1/3
25/15 x 6/7= 5/3 x 6/7= 30/21= 10/7
6/10 x 15/20= 3/5 x 3/4= 9/20
a) 1/2 + 3/4 - (3/4 - 4 - 5)
= 1/2 + 3/4 - 3/4 + 4 + 5
= (3/4 - 3/4) + (4 + 5) + 1/2
= 0 + 9 + 1/2
= 19/2
b) [9/16 + 8/(-27)] - (19/27- 7/16 - 2)
= 9/16 - 8/27 - 19/27 + 7/16 + 2
= (9/16 + 7/16) + (-8/27 - 19/27) + 2
= 1 - 1 + 2
= 2
c) -5/8 . [4/9 + 7/(-12)]
= -5/8 . (-5/36)
= 25/288
d) 7/10 . (-3/5) + 7/10 . (-2/5) - (-3/10)
= 7/10 . (-3/5 - 2/5) + 3/10
= 7/10 . (-1) + 3/10
= -2/5
e) -3/7 . 5/9 + 4/9 . (-3/7) + 2 3/7
= -3/7 . (5/9 + 4/9) + 17/7
= -3/7 . 1 + 17/7
= 2
f) 8 2/7 - (3 4/9 + 4 2/7)
= 8 + 2/7 - 3 - 4/9 - 4 - 2/7
= (8 - 3 - 4) + (2/7 - 2/7) - 4/9
= 1 - 4/9
= 5/9
h) 3.(-1/2)² - (4/5 + 8/15) : 5/6
= 3.1/4 - 4/3 : 5/6
= 3/4 - 8/5
= -17/20
\(\left(10^2+8^2+...+2^2\right)-\left(9^2+7^2+...+1^2\right)\)
\(=\left(10^2-9^2\right)+\left(8^2-7^2\right)+...+\left(2^2-1^2\right)\)
\(=\left(10-9\right)\left(10+9\right)+\left(8-7\right)\left(8+7\right)+...+\left(2-1\right)\left(2+1\right)\)
\(=19+15+...+3\)
\(=\frac{\left(3+19\right)x\left[\left(19-3\right):4+1\right]}{2}\)
\(=\frac{21.5}{2}=\frac{105}{2}=52,5\)